How the Language of Instruction Influences Mathematical Thinking Development in the First Years of Bilingual Schoolers - Bermejo, Vicente; Ester, Pilar; Morales, Isabel (Frontiers in Psychology, 2021)
Educational institutions are increasingly introducing bilingual programs in schools at early years. Accordingly, the present research study focuses on how the language of instruction has an impact on the mathematical thinking development as a consequence of using a language of instruction different from the students’ mother tongue. CLIL, learning academic content and a foreign language at the same time, is the methodology used in the schools under the present. It is, therefore, our main aim to study if the language of instruction in second language immersion programs influences the development of the first formal mathematical concepts. More specifically, if the learning of mathematical concepts in the early ages develops in a similar way if it is taught in the students’ mother tongue and if it not influenced by the language used for teaching. Or else if it can influence the formation of the first skills only in general performance or in certain areas. We tackled the situation in international schools identifying those students in first and second grades of elementary education, whose language of instruction did not match with their mother tongue and those students whose language coincided with their mother tongue. The results confirm how influencing the language of instruction is in developing mathematical thinking and being taught a formal content in a non-coincidence language which is affecting the resolution of daily life problems. However, even if a different language of instruction affects all groups, students who were taught mathematics in a second language had a similar resolution to those that the teaching language coincided with their mother tongue. It was not the case in the resolution of word problems or in the tests of mathematical competence, that showed more difficulties.